DIGITAL TECHNOLOGY-SUPPORTED PROBLEM SOLVING IN ECONOMICS EDUCATION: A SYSTEMATIC REVIEW OF EVIDENCE FROM 2021–2025 - Juwinda Lusi Apriliani; Ahmad Yusronil Wafi; Albrian Fiky Prakoso; Riza Yonisa Kurniawan (Jurnal Santiaji Pendidikan (JSP), 2026)
This study aims to systematically explore the integration of digital technology and problem-solving strategies in economic learning, with a particular focus on developing countries, especially Indonesia. A qualitative approach using the Systematic Literature Review method was applied to ten internationally indexed scientific articles published between 2021 to 2025. Data analysis was conducted using NVivo 12 Plus software to examine patterns, research gaps, and relevant best practices. The research reveals three main findings: the integration of digital technology and problem-solving strategies significantly contributes to the creation of an interactive, adaptive, and contextual learning environment through gamification, artificial intelligence, augmented reality, and interactive e-learning platforms; limitations in digital infrastructure and low technological literacy among educators are major obstacles; and pedagogical reform is needed through teacher training, curriculum modernization, and digital transformation policies. These findings provide actionable recommendations for educators and policymakers in alignment with Sustainable Development Goal 4 for inclusive and quality education. The novelty of this research lies in the conceptual synthesis that integrates digital technology with contextual problem-solving strategies in economics education in developing countries.